THE EFFECT OF ONLINE LEARNING ON STUDENTS' UNDERSTANDING IN VOCATIONAL HIGH SCHOOLS - Mohammad Syauqi (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2023)
Learning is the most important process in developing the knowledge and skills of students in educational institutions. Because since 2020 Indonesia has been hit by the COVID-19 virus which requires face-to-face learning to switch to online learning. Therefore, this study aims to find out how effective and efficient the learning process is on students' understanding. The learning process is seen from the aspects of learning (learning), teaching, and learning media. The research method used in this study uses multiple logistic regression analysis methods with data mining techniques through online questionnaires. The research site was conducted in two educational institutions under the auspices of Islamic boarding schools, namely, SMK At-Taufiqiyah and SMK Anwarul Ma'arif. The results obtained in this study showed that the teaching aspect had a significant influence with a value of 0.017 < 0.1. While the learning aspect did not have a significant influence with a value of 0.522 > 0.1 and the learning media had no significant influence with a value of 0.516 > 0.1.